SU 11248 as a novel agent for cancer treatment - Żołnierek, Jakub (Contemporary Oncology/Współczesna Onkologia, 2005)
Solid tumors can be charactrized by their resistnce to pharmacological treatment. The resistance is absolute when there is no chance for chemoterapeutic agents to induce any clinical response. On the other hand it is relative if chemotherapy can delay progression, induce objective response or even prolong survival. It can be observed till clonal selection leads to domination of malignant cells that are completely resistant to agents being administered. This is why surgery is the treatment of choice where cancer eradication is concidered. But only patients with localy advanced neoplasms and in adequate performance status can undergo operation. The problem remains in case of unresectable tumors, systemic neoplasms or patients who failed to benefit from first line treatment. Renal cell carcinoma represents tumors that are resistant to conventional treatment modalities. This is why the search for new active agents is being continued. Introduction of techniques of molecular biology helped to discover the potent role of membrane receptors for growth factors, especially its component with activity of tyrosine kinases in growth, proliferation, invasion and forming of metastatic lesions. These molecules became therapeutic targets. Efforts and budget for research regarding such targeted therapy grow continuously. The representative of that group is SU11248. The article is a report about the agent and short review of literature with special attention paid to published clinical data.